2000
DOI: 10.1099/00221287-146-6-1333
|View full text |Cite
|
Sign up to set email alerts
|

Intimin from enteropathogenic Escherichia coli mediates remodelling of the eukaryotic cell surface

Abstract: Adhesion to cultured epithelial cells by enteropathogenic Escherichia coli

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 45 publications
(5 reference statements)
2
21
0
Order By: Relevance
“…Phillips and coworkers have established an IVOC from pediatric biopsy specimens of duodenum mounted in a modified MicroSnapwell system specifically adapted for use with 2-to 3-mmdiameter biopsy samples. This IVOC system has been used mainly to study the mechanisms of virulence of ETEC (839), EPEC (840)(841)(842)(843)(844)(845)(846)(847)(848)(849)(850)(851), EHEC (852)(853)(854)(855)(856)(857), EAEC (507,858), and Salmonella (392) and the action of Stx toxins (641). Other IVOCs have been used for studies on C. jejuni (859), EPEC (692,860,861), EAEC (645,(862)(863)(864), and Shigella (865) pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phillips and coworkers have established an IVOC from pediatric biopsy specimens of duodenum mounted in a modified MicroSnapwell system specifically adapted for use with 2-to 3-mmdiameter biopsy samples. This IVOC system has been used mainly to study the mechanisms of virulence of ETEC (839), EPEC (840)(841)(842)(843)(844)(845)(846)(847)(848)(849)(850)(851), EHEC (852)(853)(854)(855)(856)(857), EAEC (507,858), and Salmonella (392) and the action of Stx toxins (641). Other IVOCs have been used for studies on C. jejuni (859), EPEC (692,860,861), EAEC (645,(862)(863)(864), and Shigella (865) pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Knutton et al (464) observed the presence of concentrated cellular F actin at the sites of attachment in fully differentiated Caco-2 cells and reported that after effacement of the microvillus, tEPEC bacteria are seen localized on a pedestal-like structure. tEPEC BFP, adhesin intimin, and several translocated T3SS effectors have been identified as intimately adhering to fully differentiated Caco-2 cells (603,604). tEPEC T3SS effectors EspA, EspB, and EspD have been shown to be required for the formation of the A/E lesions in fully differentiated Caco-2 cells (605).…”
Section: Structural and Functional Injuriesmentioning
confidence: 99%
“…It is proposed that the formation of AE lesions results in a reduction in the absorptive capacity of the intestinal mucosa, which inevitably leads to disruption of the electrolyte balance and subsequently to diarrhea. AE lesions have been demonstrated both in vivo (in biopsy specimens taken from infants with diarrhea) (24,148,173) and in vitro with a range of cell lines and organ explants (56,106,134). AE lesion formation is dependent on a number of physiological and environmental conditions (146) and is optimal in early to midlogarithmic growth at 37°C (AE lesions are not induced at 28°C).…”
Section: Introductionmentioning
confidence: 99%
“…In vivo studies using different animal models have demonstrated that in comparison to the wild type, intimin-deficient EHEC O157:H7 is defective in intestinal colonization and, in some models, in the induction of enteritis (9,10,15,25,26,36,42,47,50). Intimin exists in at least six phylogenetically distinct subtypes which exhibit marked se-quence divergence in their carboxyl-terminal cell-binding domains (1,18,19,39,40,47). The carboxyl-terminal domain of intimin mediates the interaction with Tir; however, interactions between intimin and cellular coreceptors, including ␤1-integrins and surface-localized nucleolin, have been described previously (20,43).…”
mentioning
confidence: 99%